Characterizing Occupational Low Back Pain among Surgeons Working in Ministry of Health Hospitals: Prevalence, Clinical Features and Risk and Protective Factors - Khaled S. Aseri,; Abeer A. Mulla,; Raghda M. Alwaraq,; Raneen J. Bahannan, (Journal of King Abdulaziz University: Medical Sciences, 2019)
A cross-sectional study was conducted to investigate the prevalence as well as the determinants and clinical features of occupational low back pain among surgeons working at Ministry of Health hospitals in Jeddah, Saudi Arabia by exploring its history combined with time of onset after starting the operating room work and self-appraisal of the relationship with the surgical work. Factors and predictors such as professional, socio-demographic and lifestyle factors, medical history, etc. were collected and analyzed. Two hundred and sixteen surgeons (69.9% males, mean age 39.03 years, median work: 5.00 years) responded. Prevalence of occupational low back pain was 55.8% (95% CI: 49.0%, 62.3%); high rates of inadequate management and self-treatment had a notable impact on all 4 domains. Multivariate regression showed two independent protective factors (regular physical exercise [OR = 0.27, P = 0.002] and back health education [OR = 0.41, P = 0.031] and two independent risk factors (high exposure to risky activities [OR = 1.06, P = 0.048] and presence of chronic pain other than back pain [OR = 2.59, P = 0.012]). More than one in two surgeons are likely to suffer from occupational low back pain. The protective roles of regular physical activity and back health education are highlighted